(untitled) (Al-Qamar, 2023)
English is one of the compulsory subjects at secondary level in Pakistan. The practitioners tried to improve the performance of students in the subject of English in Public schools. Therefore, the present study was aimed to examine the comparative effectiveness of teaching English through grammar translation method and computer assisted language learning at secondary level. The nature of the study was experimental. Pretest-posttest design was used. The study was conducted in Government higher secondary school Behari Colony D.I Khan. Sixty (60) students (30 participated in control group and 30 students participated in experimental group) were taken randomly on the basis of pretest. Pre-test and post-test were developed including 50 items (MSCQs and Grammar related questions). Index of Item objective Congruence (IOC) and Cronbach’s Alpha was used t estimate the content validity and reliability of pretest and posttest. Independent sample t-test was used. The study concluded that students taught though computer assisted language learning obtained high marks as compared to grammar translation method.